Hubungan Motivasi Belajar Dengan Hasil Belajar Mahasiswa Pada Mata Kuliah Media Pembelajaran Biologi - Diana Susanti; Zani Atrisa; Vivi Fitriani; Liza Yulia Sari; Lince Meriko (Fakultas Tarbiyah dan Ilmu Keguruan, Institut Agama Islam Negeri Kerinci, 2020)
Propose the research is determine the relationship of learning motivation and student learning outcomes in biology learning media courses at STKIP PGRI Sumatera Barat. The purpose of this study was to determine the relationship of learning motivation and student learning outcomes in biology learning media courses at STKIP PGRI Sumatera Barat. This research is a descriptive study. The sample are students at biology learning media course. Sample method using total sampling techniques and the research instrument was a student questionnaire. The results of this study, namely r count = 0.07 and r table = 0.266. This shows that the value of rcount < ttable which means there is no significant relationship. Thus, this research states that there is a very low and insignificant relationship between motivation and student learning outcomes in biology learning media courses at STKIP PGRI Sumatera Barat academic year 2018/2019.